Α‐Hydroxy Ketones as Masked Ester Donors in Brønsted Base Catalyzed Conjugate Additions to Nitroalkenes. Issue 15 (15th February 2018) - Olaizola, Iurre; Campano, Teresa E.; Iriarte, Igor; Vera, Silvia; Mielgo, Antonia; García, Jesús M.; Odriozola, José M.; Oiarbide, Mikel; Palomo, Claudio
Abstract: The catalyst‐controlled enantioselective direct addition reaction of enolizable esters and related carboxylic acid derivatives to π electrophiles remains a difficult synthetic transformation. In this study, the suitability of α‐hydroxy ketones as ester equivalents capable of being activated by bifunctional Brønsted base catalysts in the context of conjugate addition reactions to nitroolefins is demonstrated. The scope of the reaction, which affords the corresponding Michael adducts with very high stereoselectivity (diastereomeric ratio (d.r.) ≥95:5, up to 99 % enantiomeric excess ( ee )), and its limitations are explored, as is the aftermath elaboration of adducts into densely functionalized enantioenriched products. Abstract : Head in the right direction : The direct, asymmetric α‐functionalization of esters and related carboxylic acid derivatives is a challenge because of intrinsically difficult enolization. This problem is tackled by using α‐hydroxy ketones as enolization‐prone, tunable carboxylic acid equivalents. These templates react smoothly and in highly stereoselective manner with nitroalkenes in the presence of chiral bifunctional Brønsted base (BB) catalysts (see scheme).